(untitled) (REMUNOM, 2025)
The guava (Psidium guajava L.) is a tropical fruit tree that is resistant and productive, and its processing residue (seeds and residual pulp) is rich in nutrients and has potential to be used as an ingredient in animal feed rations. Eleven treatments were outlined using a response surface methodology, using two variables, guava flour (GF) and amoxicillin. Three animals were used per experimental unit, totaling 33 piglets with an initial age of 28 days. A variation in performance (ADG, GPD, and CA) was observed among the different treatments, decreasing both GF and antibiotic. The non-significance of the data for GPD may be due to the variability of the samples, including individual differences between animals and uncontrolled factors. The addition of high levels of GF may have affected the palatability and digestibility of the ration, leading to a reduction in feed intake by the piglets. The best feed conversion was observed with moderate levels of GF inclusion and antibiotic. The relationship between guava flour (GF) and antibiotics depends on the concentration and proportion of each component, influenced by the diet and health of the animals, and can have beneficial or antagonistic effects. Guava flour is a promising option for promoting intestinal health and improving swine performance, as long as it is properly incorporated into diets and considering factors such as concentration, source, and individual characteristics of the animals.